Smoking habit and addiction status in the workers of textile factory in - Erverdi, Osman Murat; Erikoğlu, Erdal; Bozkurt, Ali İhsan; Önal, Özgür (Journal of Dependence, 2008)
Objective: In this study researched in Abalıoğlu Manufactory of Textile about the worker’s smoking, given up cigarettes and nicotine addiction status.Method: Total 252(%52.5) workers answered the questionnaire. Approximately %85 of these workers were men and %89 of these workers graduated from high school.Results: %29.4 of the men and %8.6 of the women were smoking every day. Also, %68.6 of women and %33.2 of men were no smoking. In this study we reached that only %7.5 of smokers were addicted highly risk. %73.2 of the workers who are smoking now too, wants to given up smoking.Conclusion: Finally, as a result the workers who want to given up smoking were highly proportion and they know that the smoking’s damage, whe thought that smoking given up program is useful for the workers.
Keywords: Cigarette; addiction; worker; fagerström